PENGARUH TUJUAN PEMBANGUNAN BERKELANJUTAN TERHADAP KINERJA KEUANGAN DENGAN KEPEMILIKAN INSTITUSI SEBAGAI VARIABEL MODERATING - Wardan, Rizka Yulistiya; Rizki, Amalia (Accounting Department, Politeknik Negeri Bandung, 2024)
This study aims to obtain empirical evidence of the effect of sustainable development goals (SDGs) on financial performance with institutional ownership as a moderating variable. The paper investigates the surge in mining-related conflicts in Indonesia, examining the adverse effects on local communities and the environment, and explores the role of sustainability reporting, mandated by PJOK Nomor 51 Tahun 2017, in aligning mining companies with Sustainable Development Goals (SDGs) to address these issues. This study differs from prior research by introducing institutional ownership as a moderating variable for both dependent and independent variables, also measuring financial performance through Return on Equity (ROE). This study uses a quantitative approach using multiple linear regression analysis and moderated regression analysis. The independent variable of this study is the SDGs which are measured based on the dummy variable of the 17 SDGs objective indicators. The sample used in this study is a mining sector company that is listed on the IDX and publishes a sustainability report in 2017 – 2021. The results of this study indicate that SDGs have a negative effect on financial performance and institutional ownership cannot moderate the effect of SDGs on financial performance. The study finds that implementing SDGs is associated with lower financial performance, and institutional ownership does not moderate this impact due to insufficient attention from investors.